Analisa Rekonfigurasi Jaringan Distribusi 20 kV Pada Penyulang Berawa Untuk Menurunkan Losses dan Drop Tegangan Penyaluran Tenaga Listrik - Indra Wiguna, I Gusti Nyoman; Dyana Arjana, I Gede; Indra P, Tjok. Gede (Jurnal SPEKTRUM; Vol 6 No 2 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i02.p10, 2019)
Peak load on Berawa Feeder is very high exceeding the maximum limit set by PLN which causes Losses and high voltage drop values, so reconfiguration of Repeater via LBS Canggu Club and LBS Damai Residance is carried out, using 3 distribution points. The flow before being reconfigured in the Swamp Feeder was 242A to 180.2A, while the previous Bumbak Feeder was 82A to 144.7A. losses previous deliveries of Bumbak Feederwere 5.2kW to 22.15kW, while previous Berawa Berulang was 117.1kW to 55.11kW, drop the previous Bumbak Feeder voltagewas 102kVA to 24kVA, whereas the previous Swamp Feeder was 775.4kVA to 490.2kVA. Load surges and decreases are caused by changes in load and channel length after being reconfigured.